PELAKSANAAN REKONSILIASI FISKAL ATAS LAPORAN KEUANGAN KOMERSIAL UNTUK MENGHITUNG PAJAK PENGHASILAN BADAN PADA PT. SARI PUSPITA TAHUN 2016 - Surnamin Surnamin; Tavitri Rangkuti; Munaroh Munaroh (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
This observation was raised to find out the implementation of fiscal reconciliation on commercial financial statements whether it is in accordance with the applicable taxation and its effect on the amount of tax payable in 2016, Article 29 of Income Tax in 2016, and the amount of installments for 2016 PPh Article Sari Saripita. The research method used is a qualitative method using literature study, observation, and interviews. The conclusion shows that the implementation of fiscal reconciliation has not been in accordance with the applicable tax regulations, as a whole PT Sari Puspita has done a fairly good accounting even though there are some errors in making fiscal corrections.